Software engineering and formal methods : 12th International Conference, SEFM 2014, Grenoble, France, September 1-5, 2014. Proceedings - Salaün, Gwen; Giannakopoulou, Dimitra (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the 12th International Conference on Software Engineering and Formal Methods, SEFM 2014, held in Grenoble, France, in September 2014. The 23 full papers presented together with 3 invited and 6 tool papers were carefully reviewed and selected from 106 submissions. They are organized in topical section on program verification, testing, component-based systems, real-time and embedded systems, model checking and automata learning, program correctness, and adaptive and multi-agent systems.